Reseepy : Rice Recipe Recommendation Web-based System Using Hybrid Filtering - Mohd Azif, Bussa (Universiti Malaysia Sarawak, (UNIMAS), 2023)
A unique kind of recommendation system known as a hybrid system can be thought of as a combination of the content filtering method and the collaborative filtering method. A hybrid approach overcomes the drawbacks of using collaborative and content-based filtering separately by combining them, and it may also be more efficient in some situations. The capabilities of collaborative-based methods can be added to a content- based approach (and vice versa), or hybrid recommendation system approaches can be implemented by using content and collaborative-based methods to generate predictions separately and then combining the predictions. This project is using Hybrid filtering method implementation because here it will give more options for users to select each ingredient that could make up the recipe as well as ease users in determining recipes that could be made with only rice. The methodology that has been used for this system is Knowledge Acquisition and Documentation Structuring (KADS). This methodology is chosen because KADS offers a systematic and structured approach to gaining knowledge from domain experts, making it easier to create a knowledge base and may assist organizations in developing high-quality knowledge-based systems to enhance their decision-making processes, increase efficiency, and improve decision-making accuracy. Recipe with mainly cooked up by rice is the main ingredient that must have in this system because this project is focusing on reducing rice wastage. According to a survey of the young people, the majority of them had no notion of what they can do with the rice.Based on the survey above, all the rice recipe data will be implement for this project so that it can give wide range good recommendation rice recipe for the users especially young people so that they know what to do with the leftover rice based on the ingredients that III they have. Additionally, the designation can be done based on the survey to make sure the requirements can be done properly. Through this project, an important goal for young people was achieved that can be applied by everyone in order to reduce rice waste while also increasing user